2014
DOI: 10.1583/14-4772mr.1
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Stent-Graft Fabrics on Arterial Stiffness in Patients Undergoing Endovascular Aneurysm Repair

Abstract: Both endograft types increased PWV, while recipients of polyester covered stent-grafts showed greater PWV elevation. Further investigation will clarify the inflammatory response and the differential clinical impact of endograft types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 38 publications
(44 reference statements)
2
36
0
Order By: Relevance
“…A), suggesting potentially different mechanisms of healing in polyester and pericardial patches. Polyester is noncompliant compared to other commonly implanted vascular biomaterials, and accordingly may support less neoendothelialization …”
Section: Discussionmentioning
confidence: 99%
“…A), suggesting potentially different mechanisms of healing in polyester and pericardial patches. Polyester is noncompliant compared to other commonly implanted vascular biomaterials, and accordingly may support less neoendothelialization …”
Section: Discussionmentioning
confidence: 99%
“…There are no sufficient data regarding aortic stiffness in patients with abdominal aortic aneurysms (AAA). PWV has been found higher in patients with AAA than healthy controls, possibly indicating decreased arterial compliance . Alterations in arterial wall composition and inflammation were proposed as contributors to the increased arterial stiffness in AAA .…”
Section: Introductionmentioning
confidence: 99%
“…PWV has been found higher in patients with AAA than healthy controls, possibly indicating decreased arterial compliance. 11 Alterations in arterial wall composition and inflammation were proposed as contributors to the increased arterial stiffness in AAA. 11,12 Furthermore, PWV was related, not only to the presence, but also to the severity of CAD in symptomatic CAD patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, no further details on stent morphology and structure parameters were presented in the aforementioned papers. Nikolaos [25] investigated the effects of different endograft fabric types, such as polyester and polytetrafluoroethylene, on pulse wave velocity (PWV), which is the main parameter of hemodynamics and reflects compliance indirectly. The results indicated that the stent graft incorporated with polyester showed greater PWV and lower compliance.…”
Section: Introductionmentioning
confidence: 99%